EFFECTIVENESS OF CINEMA THERAPY TO REDUCE BULLYING BEHAVIOR IN GROUP COUNSELING FOR STUDENTS CLASS V AT SDN 1 KARANGBENDO: EFEKTIVITAS CINEMA THERAPY UNTUK MENGURANGI PERILAKU BULLYING DALAM KONSELING KELOMPOK UNTUK SISWA KELAS V DI SDN 1 KARANGBENDO - Rispika Nabila Wardah; Heriberthus Wicaksono; Fajar wahyu Prasetyo (Program Studi Bimbingan dan Konseling, 2025)
Bullying behavior which is violent behavior in peers to a child who is inferior and weaker than himself to gain advantage or satisfaction, several types of bullying, namely: (1) physical bullying, (2) social bullying (3) verbal bullying, (4) cyber bullying the phenomenon of bullying that occurs, the researcher provides a solution by providing a cinema therapy treatment in group counseling. The research uses quantitative methods using the One group Pre-test-Posttest design, design because the research does not use a control group, the subject will be given treatment with two measurements. Before the provision of group counseling and after group counseling from the results of the analysis on the normality test shows that the population data taken is normally distributed. It can be seen that the shapiro wilk significance value for the pre-test is 0.240 the value is above α 0.05 and for the post-test is 0.244 the value is above α 0.05. This shows that the bullying variables at the time of the pre-test and post-test are normally distributed. in the data analysis on the results of hypothesis testing used with the Paired Samples Statistic method, based on the results of descriptive analysis, the mean value of the pret-test was 63.625 and in the posttest 47.000. This means that there is a decrease in the value of bullying behavior which is initially high to decrease after getting treatment in the form of group counseling with cinema therapy techniques.